Self-Care Training Improves the Attitudes and Skills of Caregivers for Children with Physical Disability - Warti Ningsih; Purwanta Purwanta; Sri Hartini (Universitas Airlangga, 2018)
Introduction: The physical condition of a child with physical disabilities makes them dependent on others. Carers are the closest to children with physical disability and must have the ability to assist and teach children to do self-care activities. This study was aimed to determine the effect of self-care training on the knowledge, attitudes and skills of caregivers about the care of children with physical disability. Methods: The experiment was pre-experimental with one group pre-test-post-test design. The study was conducted on 23 caregivers who experienced caring of children with physical disability. The research instruments are Knowledge and Attitude of Self Care on Children with Physical Disability Questionnaire and Observation Sheet of Self Care on Children with Physical Disability, which have tested the validity and reliability to measure knowledge and attitude. Skill observation uses a check list with the validity test of expert opinion. Training on self-care using lecture, audiovisual, practice and discussion methods was conducted in two sessions on different days with 120 minutes per session. Data analysis used Paired Sample T-Test with significance level <0.05. Results: Self-care training significantly influenced caregivers' attitude (p = 0.038) and skill (p = 0.002), but training has no effect on caregivers' knowledge (p = 0.225). Conclusions: Self-care training improved attitudes and skills of caregivers for children with physical disability, but did not affect caregivers' knowledge.